Dua Fatwa untuk Toleransi Beragama: Relasi Muslim dan Nonmuslim dalam Perspektif Nahdhatul Ulama - Huda, Nur; Alfi, Ahmad Musonnif; Arafah, Nawal Nur (Institut Agama Islam Negeri Kerinci, 2024)
The increasing religious intolerance in Indonesia in recent years has prompted various responses from religious authorities, including Nahdlatul Ulama (NU). One of NU's efforts to address this phenomenon is through fatwas issued by the Forum Bahtsul Masail Kyai Muda Anshor (2017) and Bahtsul Masail Maudhu’iyah at the National Conference (Munas) of NU (2019), which emphasize the principle of religious tolerance, particularly concerning non-Muslim leadership and the status of non-Muslims in Muslim-majority societies. This study focuses on analyzing these two fatwas using a qualitative method through discourse analysis and interviews with key figures involved in their formulation. The findings indicate that NU fatwas not only serve as Islamic legal guidelines but also function as instruments of social reconciliation in plural societies. These fatwas offer a more inclusive and contextualized Islamic perspective, reaffirm NU’s commitment to national principles, and demonstrate that religious authority plays a crucial role in shaping tolerance discourse amid Indonesia’s socio-political dynamics. Furthermore, this study reveals that the production and reception of fatwas are influenced by social and political factors, underscoring the importance of understanding how fatwas are utilized in shaping public opinion.